Computational fluid dynamics analysis of propeller with and without fins - Wan Mohd Hasif, Wan Haron (2010)
The project objectives are to ensure that the simulation results are valid by comparison with the Standard Series Data and compare the performance of propeller with and without fins, based on Computational Fluid Dynamics (CFD) analysis. The propeller is based on Wageningen B3.55 series and made from aluminium alloy. Theoretically the fins on the back side of propeller blade will increase the thrust produce by the propeller. The methodology of this project can be divide to three parts depends on the software used; PolyWorks, SolidWorks and CosmosFloWorks. The propeller is divided into two, with and without fins. A propeller with two fins in the format of PolyWorks file after the propeller had through 3D scan process is provided, thus further 3D modeling process using PolyWorks had to be made. Other than to process the propeller to desired shape, 3D modeling also used to smoothen the surface, eliminate any defects like hole and gaps on the surface of propeller. SolidWorks is important software in this project not only because it can read the IGES file format from PolyWorks, also CosmosFloWorks is the plug-in for SolidWorks. The function of CosmosFloWorks is to analyze the performance of propellers where the value of thrust and torque is taken. Thrust is the force produced at a given speed when propeller rotates and torque is the moment act on the propeller blades. The value of thrust and torque from Standard Series Data and analysis of propeller without fins is compared to make sure the data from analysis is valid. It is observed that the value of thrust from Standard Series Data is higher than the thrust value from propeller without fins around 4.3% and 2.6% for torque. The velocity of boat is set from 3 knots to 7 knots and the slippage is not considered in the analysis. The average increase of thrust by the propeller with fins compare to propeller without fins is around 9.1% and 4.4% for torque value.